2022
DOI: 10.3389/fpsyg.2022.878531
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure and Post-traumatic Growth in Korean Adults: A Multiple Mediating Model of Deliberate Rumination, Positive Social Responses, and Meaning of Life

Abstract: BackgroundTo explore how self-disclosure leads to post-traumatic growth (PTG) in adults who have experienced traumatic events, this study identified the relationship between self-disclosure and post-traumatic growth in Korean adults. We examined a parallel multiple mediating model for this relationship.MethodsParticipants were 318 Korean male and female adult participants aged 20 years or older who had experienced trauma. We measured deliberate rumination, positive social responses, and the meaning of life as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The results indicated that self-disclosure is a crucial explanatory mechanism through which empathy relates to community workers’ PTG. Specifically, empathic community workers tended to score higher on self-disclosure, which was related to higher levels of personal growth during the pandemic, consistent with past research [ 11 , 28 ]. In this sense, high self-disclosure is not only a reflection of empathic ability but also an internal antecedent of PTG.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results indicated that self-disclosure is a crucial explanatory mechanism through which empathy relates to community workers’ PTG. Specifically, empathic community workers tended to score higher on self-disclosure, which was related to higher levels of personal growth during the pandemic, consistent with past research [ 11 , 28 ]. In this sense, high self-disclosure is not only a reflection of empathic ability but also an internal antecedent of PTG.…”
Section: Discussionsupporting
confidence: 88%
“…Previous findings suggest that PTG occurs across various populations [ 9 ] who experience traumatic events, which has attracted scholars’ interest in exploring its associated variables. Social support [ 10 ], deliberate rumination (i.e., a positive cognitive process through which one can reconstruct an existing schema and understanding the cause and meaning of an event) [ 11 , 12 ], and psychosocial interventions [ 13 ] have been reported to help people grow after traumatic events. Some studies have identified that self-disclosure [ 11 ] and emotional regulation [ 14 ] can lead to PTG.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disclosure can also promote PTG (Saltzman et al., 2018) as it may help individuals make sense of their experience, reframe it, and challenge negative beliefs. Positive social reactions have been found to be related to higher levels of growth (Ryu & Suh, 2022; Ullman, 2014). However, negative reactions are inversely related to PTG among sexual violence survivors (Ullman, 2014) and may be more strongly associated with adverse outcomes, including PTSD (Dworkin et al., 2019).…”
Section: Ptg and Sexual Violencementioning
confidence: 99%